Distribution of intellectual property rights and the development of technology suppliers - Laura Paija (The Research Institute of the Finnish Economy (ETLA), 2003)
The importance of customer relationships as a source of suppliers' innovative activity and competence accumulation has been widely recognised. The more a relationship involves collaboration and creative, non-standardised customer solutions, the more there is potential for the development of the supplier's competencies – but also for a conflict of interests pertaining to the intellectual property rights (IPRs) to the output. IPRs provide the right to economically exploit and further develop an intellectual asset. The impact of a contract allocating IPRs, and thereby partly conditioning the ex post utilisation of relationship-related knowledge, has been commonly ignored in business economics literature. The increased knowledge-intensity of products has, however, increased technology firms' concern with protecting their intellectual assets that often underlies competitive advantage and company value. This paper provides a theoretical analysis of the determinants likely to affect allocation of IPRs in buyer-supplier relationships. It also concerns consequent implications for the development of the suppliers' competitive advantage and diversification as a means to decrease possible dependence of the main customer. Contracting on asset ownership in vertical relationships inherently involves bargaining power and incentives to make relationship-specific investments. These issues have relevance in knowledge-intensive industries, such as electronics and biotechnology, in which firms feed on cross-boundary knowledge transfers, and in which successful development of small innovative firms often depends on relationships with resource-abundant established firms. – – Asiakassuhteiden on usein todettu edistävän toimittajien innovatiivisuutta sekä uuden tiedon karttumista. Asiakasyhteistyö ja tuotteiden räätälöinti lisäävät toimittajan kehittymisen – mutta toisaalta myös immateriaalioikeuksiin liittyvien intressiristiriitojen todennäköisyyttä. Immateriaalioikeudet mahdollistavat tuotteen taloudellisen hyödyntämisen ja jatkokehittämisen. Sopimus, joka määrittelee immateriaalioikeuksien jaon ja näin ollen ehdollistaa toimitussuhteeseen liittyvän tiedon myöhemmän hyödyntämisen, on yleisesti sivuutettu liiketaloustieteellisessä kirjallisuudessa. Tuotteiden tietointensiivisyyden lisääntyessä teknologiayritykset ovat kuitenkin tulleet yhä tietoisemmiksi immateriaalioikeuksien merkityksestä kilpailuedun ja yrityksen arvon perustana. Artikkelissa analysoidaan teoreettiseen kirjallisuuteen pohjautuen niitä tekijöitä, jotka vaikuttavat immateriaalioikeuksien jakoon teknologian toimitussuhteissa. Siinä myös arvioidaan immateriaalioikeuksien jaon vaikutuksia toimittajan kilpailuedun kehittymiseen. Lisäksi immateriaalioikeuksia tarkastellaan välineenä vähentää mahdollista riippuvuutta merkittävimmästä asiakkaasta. Osapuolten suhteellinen neuvotteluvoima sekä innovaation tuottamisen kannustimet liittyvät oleellisesti vertikaaliseen yhteistyöhön. Artikkelin teoreettinen malli on sovellettavissa tietointensiivisille aloille, kuten elektroniikka- ja biotekniikkateollisuuteen, joissa yritysten välinen yhteistyö on kriittistä tiedon ja osaamisen nopealle omaksumiselle ja joissa pienten innovatiivisten yritysten menestyksekäs kehittyminen riippuu usein suurista vakiintuneista toimijoista.
Keywords: 330; buyer-supplier relationships; intellectual property rights; IPRs; contracts; customisation; resource-based view; resource dependence; bargaining power; asiakas-toimittajasuhteet; immateriaalioikeudet; sopimukset; tuotteiden räätälöinti; voimavarapohjainen yrityksen teoria; resurssiriippuvuus; neuvotteluvoima; Immaterialgüterrechte; Lieferanten-Kunden-Beziehung; Industrieökonomik; Innovationsmanagement; Theorie